Outside Front Cover: Volume 4 Issue 2. Issue 2 (27th December 2022) - Chen, Jinxing; Lee, Michael; Qiu, Yinghua; Wu, Chaolumen; Li, Bo; Yin, Yadong
Abstract : Outside front cover image : Interfacial solar steam generation is an alternative method for clean water production, where enhanced evaporation rates are crucial. This work proposes using a high internal phase emulsion (HIPE) to template the synthesis of 3D hierarchically porous evaporators. The HIPE‐templated synthesis allows efficient fabrication of desired 3D shapes with minimal material waste. Engineering the overall shape and internal pores of the 3D evaporator can suppress heat loss and effectively collect thermal energy from the surroundings, thereby boosting the evaporation rate. The HIPE‐templated synthesis is a simple and efficient method to produce a variety of porous polymers with a wide range of promising applications. (DOI: https://doi.org/10.1002/smm2.1140 )